THE CONCEPT OF ZERO SEMANTIC TRANSFER (ON THE BASIS OF ENGLISH LOAN WORDS IN THE UKRAINIAN LANGUAGE) - Bytkivska, Y. V.; Tkachivska, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim of the article is to analyze zero meaning transfer of English loan words i.e. when the loan word preserves its meaning without any changes, at the initial stage of entering the Ukrainian lexical-semantic system. To achieve the goal of the research modern English loan words used in speech, fiction, mass media, as well as in dictionaries have been collected and systematized; the frames of meaning of englisms have been determined; the specifics of functioning of these lexemes in the Ukrainian language have been studied. The results show that zero meaning transfer is rather common tendency in Ukrainian since it reflects the necessity of the language system to mark new notions caused by globalization. On the other hand, the use of some borrowings is apparently reckless as they denote the notions that have their established native lexemes which therefore are able to render the whole range of the required meaning.